The Makings of a Good Law School? - Michael Trebilcock (Legal Education Review)
Over the course of an academic career spanning about 27 years, I have seen inside many different law schools. I undertook my initial legal training at the University of Canterbury Law School in Christchurch, New Zealand, between 1959 and 1962. I entered law school out of a country high school. In my first year, there was only one full-time academic member of staff, the balance of the instruction being undertaken mostly by young or struggling practitioners who required extra income. By the end of my degree, the school had inched up to three full-time academic staff. Moreover, many of the students were part-time, with students after their first or second year simultaneously clerking with local law firms. On moving to the University of Adelaide Law School in 1963, as a tutor while simultaneously undertaking an LL M by thesis, I encountered a law school which initially had six or seven full-time members of staff, with a great deal of practitioner instruction and much part-time study by students. By the end of my time at Adelaide in 1969, the Faculty had increased to perhaps 12 or 14 full-time staff members. On moving to the McGill Law School in Montreal in 1969, I encountered my first full-blown law school, with perhaps 25 full-time members of faculty and a full-time student body and national programmes offering degrees in both common and civil law, as well as a significant full-time graduate programme. On moving to the University of Toronto Law School in 1972, I joined what was perhaps regarded as the pre-eminent academic law school in Canada, with strong and proud traditions of innovation in legal education, although at that time afflicted with a degree of parochialism and complacency that was at variance with these traditions. During the ensuing 18 years at the University of Toronto, I took a leave at the University of Chicago law school in 1976 and was exposed for the first time to a law school with a strong commitment to interdisciplinary studies, especially, in my case, law and economics. A further leave at the Yale Law School in 1985 exposed me to an even broader range of theoretical and interdisciplinary perspectives on law. Both Chicago and Yale also have strong traditions of organised collegial forums for review of research work in progress. In the course of the last year, I have been associated with two law school reviews on a pending change of command: first, our own Law School and secondly the University of British Columbia Law School. And most recently, I have spent four weeks at the University of Melbourne Law School, revisited my first academic home, the University of Adelaide Law School and made brief visits to Monash and the University of Sydney law schools.